2018
DOI: 10.1371/journal.pone.0208540
|View full text |Cite|
|
Sign up to set email alerts
|

A phenotype of increased sleepiness in a mouse model of pulmonary hypertension and right ventricular hypertrophy

Abstract: The relationship between cardiovascular disease and abnormalities in sleep architecture is complex and bi-directional. Sleep disordered breathing (SDB) often confounds human studies examining sleep in the setting of heart failure, and the independent impact of isolated right or left heart failure on sleep is difficult to assess. We utilized an animal model of right heart failure using pulmonary artery banding (PAB) in mice to examine the causal effect of right heart failure on sleep architecture. Four weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Previous data have shown that apoE-knockout mice on an HFD developed PH; clearly, these animals also developed an evident level of pulmonary atherosclerosis, which may be a bias in the correlation of IR with PH ( 12 ). Our model of obesity-induced IR showed an increase in pulmonary artery pressure, with an RVSP variation of 6–9 mmHg and also confirmed after catheterization, which was not based on left ventricular dysfunction and seems to be similar to other PH animal models induced by other methods ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 85%
“…Previous data have shown that apoE-knockout mice on an HFD developed PH; clearly, these animals also developed an evident level of pulmonary atherosclerosis, which may be a bias in the correlation of IR with PH ( 12 ). Our model of obesity-induced IR showed an increase in pulmonary artery pressure, with an RVSP variation of 6–9 mmHg and also confirmed after catheterization, which was not based on left ventricular dysfunction and seems to be similar to other PH animal models induced by other methods ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 85%